Energy Dissipation in Black Phosphorus Heterostructured Devices. Issue 2 (23rd November 2018) - Ali, Fida; Ahmed, Faisal; Yang, Zheng; Moon, Inyong; Lee, Myeongjin; Hassan, Yasir; Lee, Changgu; Yoo, Won Jong
Abstract: Two‐dimensional (2D) black phosphorus (BP) has attracted increasing interest for next‐generation solid‐state device applications due to its unique blend of versatile properties. The ultrathin physique and low thermal conductivity (40–20 Wm −1 K −1 ) of BP make it susceptible to premature Joule breakdown under moderate electric field induced by inefficient and nonhomogeneous energy dissipation. Here, it is reported that the back‐gate BP device suffers Joule breakdown merely under 4 MV m −1 electric field value with the centrally localized fracture. The spatial micro‐Raman spectroscopy confirms uneven thermal spreading in BP channel with the center being 20% hotter than the lateral ends. Furthermore, to mitigate the early breakdown and uneven spreading, vertical van der Waals structure is assembled. The results show that the vertical BP device exhibits 230 times higher field strength and one order enhancement in power sustainability than those of lateral devices due to the integration of thermally favorable constituent materials and formation of the optimal path for self‐heat removal. Abstract : The power dissipation in two‐dimensional (2D) black phosphorus (BP) is studied by carrying spatial micro‐Raman spectroscopy and electrical breakdown. It shows nonuniformity of Joule heat spreading in lateral BP devices. The electrical breakdown behavior is improved by forming vertical van‐der Waals structure which provides efficient cooling path for spreading the excessive thermal energy induced during device operation under high electric field.